2014
DOI: 10.1007/s40521-014-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

New Targets for Immune Modulation in Asthma

Abstract: Opinion statementCurative treatment for asthma poses a challenge. Standard asthma therapy is primarily based on immunosuppressive and bronchodilator drugs, which confer shortterm symptom relief but do not cure the disease. Approximately 5-10 % of asthma patients do not respond to conventional therapy. Currently, allergen-specific immunotherapy (SIT) is the only available curative treatment for allergic asthma patients, and is most effective in monosensitized individuals. Toll-like receptor (TLR) 4 and TLR9 ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The pathobiology of asthma is complex and poorly understood (2-4). While current therapies ameliorate symptoms, none affect the long-term trajectory of lung function decline (5)(6)(7). Despite the significantly high global prevalence of asthma, and the magnitude of research Abnormal wound repair has been observed in the airway epithelium of patients with chronic respiratory diseases, including asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The pathobiology of asthma is complex and poorly understood (2-4). While current therapies ameliorate symptoms, none affect the long-term trajectory of lung function decline (5)(6)(7). Despite the significantly high global prevalence of asthma, and the magnitude of research Abnormal wound repair has been observed in the airway epithelium of patients with chronic respiratory diseases, including asthma.…”
Section: Introductionmentioning
confidence: 99%